Investigating Single-Molecule Molecular Inversion Probes for Medium-Scale Targeted DNA Methylation Analysis - Roy B. Simons; Hieab H. H. Adams; Manfred Kayser; Athina Vidaki (Epigenomes)
Background: Epigenetic biomarkers, particularly CpG methylation, are increasingly employed in clinical and forensic settings. However, we still lack a cost-effective, sensitive, medium-scale method for the analysis of hundreds to thousands of user-defined CpGs suitable for minute DNA input amounts (<10 ng). In this study, motivated by promising results in the genetics field, we investigated single-molecule molecular inversion probes (smMIPs) for simultaneous analysis of hundreds of CpGs by using an example set of 514 age-associated CpGs (Zhang model). Methods: First, we developed a novel smMIP design tool to suit bisulfite-converted DNA (Locksmith). Then, to optimize the capture process, we performed single-probe capture for ten selected, representative smMIPs. Based on this pilot, the full smMIP panel was tested under varying capture conditions, including hybridization and elongation temperature, smMIP and template DNA amounts, dNTP concentration and elongation time. Results: Overall, we found that the capture efficiency was highly probe-(and hence, sequence-) dependent, with a heterogeneous coverage distribution across CpGs higher than the 1000-fold range. Considering CpGs with at least 20X coverage, we yielded robust methylation detection with levels comparable to those obtained from the gold standard EPIC microarray analysis (Pearsons’s r: 0.96). Conclusions: The observed low specificity and uniformity indicate that smMIPs in their current form are not compatible with the lowered complexity of bisulfite-converted DNA.